2021
DOI: 10.22331/q-2021-06-02-465
|View full text |Cite
|
Sign up to set email alerts
|

Quantum advantage from energy measurements of many-body quantum systems

Abstract: The problem of sampling outputs of quantum circuits has been proposed as a candidate for demonstrating a quantum computational advantage (sometimes referred to as quantum "supremacy"). In this work, we investigate whether quantum advantage demonstrations can be achieved for more physically-motivated sampling problems, related to measurements of physical observables. We focus on the problem of sampling the outcomes of an energy measurement, performed on a simple-to-prepare product quantum state – a problem we r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 91 publications
(264 reference statements)
0
2
0
Order By: Relevance
“…The pioneering works of Feynman [1,2], Bennett and Brassard [3], Deutsch [4], Shor [5], and others have strongly established that using quantum resources in computation, communication, and metrology, one can obtain certain advantages usually referred to as quantum advantage. Subsequent theoretical and experimental works including Google's recent experimental demonstration of quantum advantage [6] have further established this fact ( [7][8][9][10][11][12] are a few recent examples). A common feature of all these works is that quantum advantage requires nonclassical states, or in other words, the quantum states having no classical analog.…”
Section: Introductionmentioning
confidence: 94%
“…The pioneering works of Feynman [1,2], Bennett and Brassard [3], Deutsch [4], Shor [5], and others have strongly established that using quantum resources in computation, communication, and metrology, one can obtain certain advantages usually referred to as quantum advantage. Subsequent theoretical and experimental works including Google's recent experimental demonstration of quantum advantage [6] have further established this fact ( [7][8][9][10][11][12] are a few recent examples). A common feature of all these works is that quantum advantage requires nonclassical states, or in other words, the quantum states having no classical analog.…”
Section: Introductionmentioning
confidence: 94%
“…Quantities that first come to mind here are measurements of k-point correlation functions of the type b † i b j . First steps towards this have been taken by Novo et al (2021) where it has been shown that one can run a Stockmeyer argument for the task of reproducing the statistics of an energy measurement of a local Hamiltonian. Deviating from the mindset of quantum random sampling Baez et al (2020) have shown a quantum advantage for the estimation of dynamical structure factors, bringing the insight that performing measurements on quantum states arising from time evolution under local Hamiltonians is BQP complete (Nagaj, 2012;Nagaj and Wocjan, 2008;Vollbrecht and Cirac, 2008) closer to reality.…”
Section: Relation To Analogue Quantum Simulationmentioning
confidence: 99%